Critical assessment of CSR of a specific company - Ikonnikova, Ekaterina; Křečková Kroupová, Zuzana, 1972-; Jašek, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This thesis focuses on assessing the CSR of a company X, i.e. on evaluating how successful their CSR programs, which focus on supporting younger generations, based on a measuring model. To fulfil the aim of the thesis, the following four research questions were selected: “How is implemented CSR matching predefined CSR goals?”, “How sufficient are the policies in place?”, “How successful are the CSR programs?” and “Do CSR practices have an influence on how consumers and employees view the company?”. The answers to the research questions are found through research, which is focused on: analysing CSR practices that have been implemented by the company X and their possible effect on employee loyalty as well as consumer views of the company, identifying the potential link between employee loyalty and CSR programs implemented, looking for the potential link between consumer views of the company and CSR programs implemented as well as making suggestions on possible improvements to the company.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses